3 Standarisasi Resep Kue Pinyaram Itam Di Kanagarian Alahan Panjang Kabupaten Solok - Nenda, Welly Afrita; Baidar, Baidar; Elida, Elida (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aims to find a standard cake recipe pinyaram Itam, and the quality of the cakes pinyaram Itam. This research is a qualitative and quantitative research using mixed methods (Mixed Method). This research was conducted in Kanagarian Alahan Panjang from the date of July 28, 2016 until August 28, 2016. The data source is two fold: a source of qualitative data obtained from people who are good at making cakes pinyaram itam, the source of quantitative data obtained from five panelists limited good at making cakes pinyaram itam in Kanagarian Alahan Panjang. Based on the quantitative results of organoleptic standardization cake recipe pinyaram Itam which has been converted followed by organoleptic tests found the quality of the cake pinyaramitam include: form pinyaram Itam (neat), forms the central part (round), the shape of the edge (lace), center of volume (expands) , color (purple), aroma (the aroma of black rice), middle texture (soft), texture edge (dry), the center of the cavity (hollow) and taste (sweet), flavor (black rice).Keywords: standardization, cake recipe pinyaram itam, quality.